2022
DOI: 10.1039/d2py01146h
|View full text |Cite
|
Sign up to set email alerts
|

Dual cross-linking strategy to prepare fluorine-containing poly(arylene ether nitrile) films with a low dielectric constant and ultra-low water uptake

Abstract: Low k-value in humid environment is an important parameter for low dielectric materials, as k-value is very sensitive to humidity. In order to obtain low dielectric constant and improve the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Lei et al 25 prepared PEN/fullerenes composite films, and fullerenes lowered the dielectric constant of this composite film due to its special hollow cage structure. Cao et al 35 designed and synthesized a series of PEN copolymers containing trifluoromethyl groups with two cross‐linking points of nitrile and propylene groups (DnAF‐PEN). By producing a highly cross‐linked structure, the dielectric constant was reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Lei et al 25 prepared PEN/fullerenes composite films, and fullerenes lowered the dielectric constant of this composite film due to its special hollow cage structure. Cao et al 35 designed and synthesized a series of PEN copolymers containing trifluoromethyl groups with two cross‐linking points of nitrile and propylene groups (DnAF‐PEN). By producing a highly cross‐linked structure, the dielectric constant was reduced.…”
Section: Resultsmentioning
confidence: 99%
“…From this analysis, it is shown that adding HCP to the PI matrix may significantly weaken the polymer chain orientation and inter‐chain interactions, and thus reduce the stacking density of the polymer chains. [ 26 ]…”
Section: Resultsmentioning
confidence: 99%
“…From this analysis, it is shown that adding HCP to the PI matrix may significantly weaken the polymer chain orientation and inter-chain interactions, and thus reduce the stacking density of the polymer chains. [26] PI films often have a deep yellow color due to the formation of charge transfer complexes (CTC) within or among molecular chains. [27] For instance, Kapton films are generally brown or reddish-brown in color due to the large number of conjugated heterocyclic structures in the molecular structure, which results in strong intramolecular and intermolecular charge transfer.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16] It is noteworthy that the nitrile groups on the PEN chain segments can not only undergo cross-linking reactions at a temperature to transform the linear structure into three-dimensional network, resulting in high T g and T 5% , 8,17,18 but also have good adhesion to many substances. 19,20 Nevertheless, the dimensional stability, frequency stability, and intrinsic thermal conductivity of PENs are not well, which affect the safety and application of electronic fields in some extent. Divinyl siloxanebisbenzocyclobutene (BCB) as a thermosetting resin could be used in a variety of microelectronics applications owning to its advantages [21][22][23][24] of low-dielectric constant (2.6-2.7), thermal dimensional stability, outstanding T g , chemical stability, and mechanical processing.…”
Section: Introductionmentioning
confidence: 99%
“…The unique molecular structure provides a sea of advantages, such as high thermal stability, good mechanicals, and tunable dielectric properties via cross‐linking or crystallization 13–16 . It is noteworthy that the nitrile groups on the PEN chain segments can not only undergo cross‐linking reactions at a temperature to transform the linear structure into three‐dimensional network, resulting in high T g and T 5% , 8,17,18 but also have good adhesion to many substances 19,20 . Nevertheless, the dimensional stability, frequency stability, and intrinsic thermal conductivity of PENs are not well, which affect the safety and application of electronic fields in some extent.…”
Section: Introductionmentioning
confidence: 99%